The war that saved my life - Bradley, Kimberly Brubaker 1967- (Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2015)
A young disabled girl and her brother are evacuated from London to the English countryside during World War II, where they find life to be much sweeter away from their abusive mother